Carbon footprint of India’s groundwater irrigation - Rajan, Abhishek; Ghosh, Kuhelika; Shah, Ananya (Informa UK Limited, 2020)
India has an intricate nexus of groundwater irrigation, energy and climate. Subsidized electricity supply has led to unregulated groundwater pumping, causing a decrease in groundwater level and increase in carbon emissions. This complex nexus necessitates estimation of carbon emissions from groundwater irrigation. The study uses actual pumping data on 20.5 million groundwater structures from the Fifth Minor Irrigation Census (reference year 2013–14) to estimate carbon emissions. The estimates show that groundwater irrigation emits 45.3–62.3 MMT of carbon annually, contributing 8–11% of India’s total carbon emission. This analysis shows deep tubewells have a huge carbon footprint, and their growing number is a serious environmental concern. Spatial analysis reveals India’s western and peninsular region, which houses 85% of the country’s over-exploited groundwater blocks, contributes most to carbon emission. Moreover, this region hosts 27 districts which are groundwater–energy–climate nexus hotspots, together accounting for 34% of carbon emissions from groundwater irrigation. Comparison with the previous estimate reveals that carbon emission from groundwater irrigation nearly doubled between 2000 and 2013. Findings of this study are vital to the discourse on the increasing environmental costs of groundwater pumping in the country and will contribute to carbon emission mitigation strategies.